The Effect of Activator Addition to the Compost with Biopore Infiltration Hole (BIH) Method - Yenni Ruslinda; Rizki Aziz; Larasati Sekar Arum; Novita Sari (Jurnal Ilmu Lingkungan, 2021)
The composition of organic waste reaches 59% of the total municipal solid waste in Indonesia. One way to process organic waste is composting by utilizing microorganisms to break down waste into compost. Naturally, the composting process took a long time but can be accelerated by adding microorganisms to the activator. This study analyzes the quality and quantity of compost using the Biopore Infiltration Hole (BIH) method with activator addition. Composting was duplicated in the yard area with clay soil type and water infiltration rate of 0,3 cm/hour. The BIH was made in a 10 cm diameter, a 100 cm depth, and the distance between the holes was 50 cm. Composting variations consist of variations in the composition of the raw materials and the activators' uses. Variations in the raw material composition consisted of 100% yard waste, 100% food waste, 50% yard waste and 50% food waste, and 70% food waste and 30% yard waste. In contrast, the activator variations consisted of no activator, EM4 activator, and Stardec activator. Compost analysis consists of maturity, quality of physical and macro elements, and quantity of compost. The results showed that all variations of composting had met the standard of maturity and quality of physical and macro elements according to SNI 19-7030-2004. The addition of activator affected composting time and compost quantity. The composting time in BIH with activator ranges from 41-60 days. In BIH without activator ranges from 65-75 days, there was a reduction in composting time by 15-25 days with the activator addition. However, the activator addition caused reducing the compost quantity by 10-20%. The selection of compost variations by scoring results in compost with a composition of 50% yard waste and 50% food waste and the addition of Stardec activators was the best variation in terms of compost maturity, quality, and quantity.